Development of Interactive Digital Learning Media to Improve Fiqh Understanding in Islamic Elementary School Students - Raniatul Muna (Journal of Indonesian Primary School, 2025)
The development of interactive digital learning media has emerged as a crucial strategy to enhance students' understanding of Fiqh in Islamic primary school. This study aimed to design, implement, and evaluate the effectiveness of digital interactive learning media in improving Fiqh comprehension among primary Islamic school students. A mixed-method approach was employed, involving 60 students from a Islamic primary school in Aceh Province. Data were collected using pre-test and post-test assessments, observation sheets, and student questionnaires to measure comprehension levels and engagement. The results indicated a significant improvement in students’ understanding of Fiqh concepts, with an average score increase from 65.2 to 85.7 (SD = 7.3) after using the interactive digital media. Observations and questionnaires also revealed increased student motivation, active participation, and positive learning attitudes. These findings suggest that the integration of interactive digital tools into Fiqh instruction can effectively facilitate knowledge acquisition and engagement, providing practical implications for curriculum design and teaching strategies in Islamic primary education. Future research should explore long-term effects and scalability across multiple institutions.